ANALYSIS OF GEOTHERMAL WELL PRODUCTION CAPABILITY BASED ON OUTPUT CURVE AND WELLBORE SIMULATION IN AAP FIELD - Putri, Alayda Aisyah; Malinda, Marmora Titi; Yulia, Prayang Sunny; Pramadika, Havidh (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2025)
The assessment of geothermal well production capability plays a crucial role in optimizing geothermal energy generation systems. This study focuses on evaluating the performance of two geothermal wells, ZM-42 and ZM-31, located in the AAP Field, by developing output curves through wellbore simulation techniques. The analysis utilizes field production test results, well casing configuration data, and PTS (Pressure, Temperature, and Spinner) survey data to generate key parameters such as wellhead pressure, fluid flow rate, fluid temperature, enthalpy, and vapor fraction (dryness). These parameters are essential for understanding the thermal and flow characteristics of each well. Wellbore simulations were conducted using specialized software to replicate the flow behaviour of geothermal fluids within the well system. The output curves produced provide a graphical representation of the relationship between wellhead pressure and mass flow rate under various operating conditions. Validation of the simulation was done by comparing the generated curves with actual field measurements. The results show that well ZM-31 demonstrates a higher production capability compared to ZM-42. ZM-31 recorded a flow rate of 96.61 kg/s and an enthalpy of 1134.5 kJ/kg, with a vapor fraction of 0.14. In contrast, ZM-42 exhibited a lower flow rate of 85.60 kg/s, enthalpy of 1027.7 kJ/kg, and a vapor fraction of 0.11. These differences indicate superior separation efficiency and thermal performance in ZM-31. Furthermore, ZM-31’s production is dominated by a single feed zone, while ZM-42 relies on multiple contributing zones. In conclusion, based on output curve analysis and well simulation results, ZM-31 is recommended as the primary production well for further optimization in the AAP geothermal field, contributing to more efficient and reliable energy output.